2012
DOI: 10.1001/archoto.2012.237
|View full text |Cite
|
Sign up to set email alerts
|

Frequent Association of Cochlear Nerve Canal Stenosis With Pediatric Sensorineural Hearing Loss

Abstract: Cochlear nerve canal stenosis is associated with SNHL, and the degree of stenosis predicted the degree of SNHL. In addition, the presence of CNC stenosis with additional inner ear abnormalities may affect the severity of SNHL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 20 publications
1
27
0
1
Order By: Relevance
“…From an earlier study, the external dimensions of the cochlea (height and diameter) were found to be similar to the normal cochlea ( 17 ), therefore, it is appropriate to include IP-III under the incomplete partition anomalies. In addition, labyrinthine segment of the facial nerve is located almost above the cochlea ( 20 ) instead of making a gentle curve around the basal turn on axial sections. The labyrinthine segment of the facial nerve is the most superior structure in the temporal bone.…”
Section: I-inner Ear Malformationsmentioning
confidence: 99%
See 1 more Smart Citation
“…From an earlier study, the external dimensions of the cochlea (height and diameter) were found to be similar to the normal cochlea ( 17 ), therefore, it is appropriate to include IP-III under the incomplete partition anomalies. In addition, labyrinthine segment of the facial nerve is located almost above the cochlea ( 20 ) instead of making a gentle curve around the basal turn on axial sections. The labyrinthine segment of the facial nerve is the most superior structure in the temporal bone.…”
Section: I-inner Ear Malformationsmentioning
confidence: 99%
“…The CA is considered hypoplastic ( Figure 9a ) if the width is less than 1.4 mm ( 20 ). The CA is considered to be aplastic when the canal is completely replaced by bone or there is no canal on mid-modiolar view ( Figure 9b ).…”
Section: I-inner Ear Malformationsmentioning
confidence: 99%
“…The BCNC encases the cochlear nerve from the fundus of the internal auditory canal (IAC) to the base of the cochlear modiolus; therefore, it has been suggested that BCNC stenosis serves as a marker of anatomic or functional deficiency of the cochlear nerve . Several studies have described an association between stenosis of the bony cochlear nerve canal and congenital SNHL …”
Section: Introductionmentioning
confidence: 99%
“…In particular, an absent cochlear nerve canal impacts cochlear implant candidacy and has related prognostic implications. 78,79 In addition, once cochlear implantation has been completed, MRI can no longer provide meaningful diagnostics for that ear due to the implant-associated image distortion. Also, preparation for MRI after implantation requires addressing the internal magnet, which involves an additional procedure.…”
Section: Discussionmentioning
confidence: 99%